Digital Photometric Method for Determining Degree of Harvest Maturity and Ripeness of ‘Sinta’ Papaya (Carica papaya L.) Fruits - Domingo, Dulce L.; Serrano, Banyuhay P.; Serrano, Edralina P.; Del Rosario, Ernesto J. (2012)
The degree of ripeness of ‘Sinta’ papaya (Carica papaya L.) fruits was determined by taking digital pictures of fruits at varying stages of ripeness, followed by color analysis of the digital photographs based on the generated red (R), green (G) and blue (B) color values of the photographs using a computer software (RGB Analysis of Image Color). The stages of fruit ripeness were classified based on RGB values, visual characteristics, as well as total soluble solids, total carbohydrates, titratable acidity and firmness, of the fruits; these parameters were correlated with the stages of ripeness. There was a significant increase in total soluble solids and total carbohydrates of the fruits from ripening stage 1 (green) to stage 2 (with tinge of yellow) and a significant decrease in firmness as the fruits ripened. No significant change was observed in titratable acidity of the fruits during ripening. Firmness and total carbohydrates showed the strongest correlation with degree of ripeness among the four parameters studied. From the slopes in plots of RGB values versus firmness, binary and ternary color functions were formulated in order to measure the degree of fruit ripeness. The correlation coefficients were 0.9387 and 0.9497 for plots (versus fruit firmness) of the binary and ternary color functions, respectively. The results showed that the photometric method, using a digital camera combined with software for color analysis, can help to quantitatively determine the degree of maturity and ripeness of ‘Sinta’ papaya fruits.
Keywords: Harvesting of fruit; Fruit ripening; Papaya